2020
DOI: 10.3390/genes11020214
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Microsatellites Mined from Transcriptome Data and the Development of Novel Markers in Paeonia lactiflora

Abstract: The insufficient number of available simple sequence repeats (SSRs) inhibits genetic research on and molecular breeding of Paeonia lactiflora, a flowering crop with great economic value. The objective of this study was to develop SSRs for P. lactiflora with Illumina RNA sequencing and assess the role of SSRs in gene regulation. The results showed that dinucleotides with AG/CT repeats were the most abundant type of repeat motif in P. lactiflora and were preferentially distributed in untranslated regions. Signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…We also found that the microsatellites located in CDS regions were dominated by tri-nucleotides, while other SSR motifs accounted for a small proportion. This was common in many plants, such as Phoenix dactylifera L. (Zhao et al, 2013), Tetraena mongolica (Dang et al, 2020), and Paeonia lactiflora (Wan et al, 2020). Compared to other repeat types, tri-nucleotide is less likely to frame-shift mutations in coding regions (Metzgar et al, 2000).…”
Section: Microsatellite Distribution In Different Genic Regionsmentioning
confidence: 99%
“…We also found that the microsatellites located in CDS regions were dominated by tri-nucleotides, while other SSR motifs accounted for a small proportion. This was common in many plants, such as Phoenix dactylifera L. (Zhao et al, 2013), Tetraena mongolica (Dang et al, 2020), and Paeonia lactiflora (Wan et al, 2020). Compared to other repeat types, tri-nucleotide is less likely to frame-shift mutations in coding regions (Metzgar et al, 2000).…”
Section: Microsatellite Distribution In Different Genic Regionsmentioning
confidence: 99%
“…polymorphism and specific function in a species (Lebedev et al, 2020), where for example SSRs in the 5'UTR are more polymorphic compared to those in the 3'UTR (Wan et al, 2020). SSRs found in the 5'UTR have an effect on gene transcription and regulation, whereas SSRs found in the 3'UTR are involved in gene silencing and transcription slippage (Li et al, 2004;Varshney et al, 2005).…”
Section: P R E S Smentioning
confidence: 99%
“…Simple sequence repeat markers (SSRs, microsatellites) were developed for tree peonies (Gai et al 2012;Gao et al 2013;Guo et al 2017;Homolka et al 2010;Hou et al 2011a, b;Wang et al 2009;Wu et al 2014;Yu et al 2013;Zhang et al 2011Zhang et al , 2012 and to a lesser extent for P. lactiflora Pall. (Cheng et al 2011;Gilmore et al 2013;Ji et al 2014;Li et al 2011;Wan et al 2020). In addition to identifying cultivars and species, DNA markers can be used to identify hybrid origin, to study genetic diversity and relationships, and for linkage mapping.…”
Section: Introductionmentioning
confidence: 99%